There's a storm brewing : an experimental cooperative brewery in the south of Johannesburg - Page, Robert James (My University, 2016)
In Johannesburg, sociability and drinking culture have complex pasts. Beer, especially, is tied up in multiple significances: a prominent role in many traditional African cultures; later, co-opted as a means of control by South Africa’s former government; rising as a strong socially cohesive identifier in emerging popular culture; and now, turning a new face to a culture of experimentation and excellence in the craft of brewing with one foot in the realm of wine snobs, and connoisseurs. I investigate my own family’s history of brewing in seventeenth century England as an introduction to a brief history of two important global, social drinking cultures – Mediterranean and Northern European – and apply this cultural lens to a reading of local, Johannesburg beer drinking. Beer can be understood as a strong symbolic agent in the construction of imagined communities and the realisation of experiences in multiple simultaneities of space and time. I investigate these imagined realities, and interrogate the current disjuncture between the consumption and production of beer. Finally, I propose a hybrid brewing facility as an architectural intervention in Booysens Reserve, a small industrial suburb in the south of Johannesburg, and look towards the unique conditions to explore, and opportunities for intervention which this part of the city, the intersection of multiple cultures, landscapes and industries, has to offer.
Thesis (M.Arch. (Professional))--University of the Witwatersrand, Faculty of Engineering and the Built Environment, School of Architecture and Planning, 2016.
Keywords: Brewing industry--South Africa--Johannesburg; Beer industry--South Africa